Republic of Serbia : Financial Sector Assessment Program Update; Technical Note on Insurance Sector. (IMF Staff Country Reports; Country Report ;, 2010)
This Technical Note analyzes the insurance sector in Serbia. The Serbian insurance sector remains small and underdeveloped. Over the last three years, the market experienced little growth in real terms mainly owing to weak economic growth, fierce price competition among the growing number of players, and premium payment difficulties in the industrial sector, which forced many corporate policyholders to cancel their insurance. The paper highlights that the Serbian insurance sector is well capitalized relative to its overall net risk exposure.